Pengaruh Independen Auditor terhadap Kinerja Auditor Internal di Lembaga Amal Muhammadiyah di Kabupaten Ponorogo - Titin Eka Ardiana; Nanang Cendriono; Rizki Rachmadia (SUSTAINABLE, 2026)
This study aims to determine the effect of independence on the performance of internal auditors in Muhammadiyah Business Associations (AUM) of Ponorogo Regency. The problem addressed in this study is the partial effect of independence on the performance of AUM internal auditors. The method used in this study is a quantitative research approach. The data utilized in this study are primary data in the form of questionnaires obtained from respondents' answers. The population in this study consists of 30 internal auditors from the Muhammadiyah Business Associations (AUM) of Ponorogo Regency. The sampling method employed in this study is purposive sampling.The data analysis technique used is simple linear regression using SPSS version 16 software. The results of the study prove that independence has a positive and significant effect on the performance of internal auditors at AUM in Ponorogo Regency. This implies that the higher the independence, the more the performance of the internal auditors will increase.